Early-life hearing loss induces persistent cognitive deficits: evidence from human data and a mouse model with environmental intervention - Zhou, Xuehua; Yu, Huiqian; Wang, Yiru; Chen, Kaizheng; Shen, Xia (Frontiers in Aging Neuroscience, 2025)
Hearing loss during early life has been linked to later cognitive decline, but the underlying neural mechanisms remain unclear. To investigate the cognitive impact of early hearing loss in humans, adults aged 18–40 years with severe childhood hearing loss were evaluated using standardized cognitive assessments. In parallel mouse studies, a mouse model of sensorineural hearing loss was established to assess memory function, hippocampal microglial activation, Tau phosphorylation, and synaptic integrity at 1 and 4 months post-insult. Mice were also exposed to environmental enrichment to test its therapeutic effects. Our data showed that individuals with early hearing loss had a significantly increased risk of cognitive impairment (OR = 1.010, 95% CI: 1.002–1.017, p = 0.011). Hearing-impaired mice showed progressive memory deficits, neuroinflammation, Tau hyperphosphorylation, and synaptic loss in the hippocampus. Environmental enrichment improved cognitive performance in affected mice. This study demonstrates that early-life hearing loss induces persistent cognitive deficits in humans, and induces hippocampal pathology in mice. Environmental enrichment effectively improve cognitive performance in affected mice, suggesting that timely interventions may help mitigate adverse outcomes.